Noble metal-free CZTS electrocatalysis: synergetic characteristics and emerging applications towards water splitting reactions - Dhawale, Somnath C.; Digraskar, Renuka V.; Ghule, Anil V.; Sathe, Bhaskar R. (Frontiers in Chemistry, 2024)
This review provides a comprehensive overview of the fabrication of CZTS nanoparticles(NPs) and their application towards water electrocatalysis. Various aspects, including surface modification, heterostructure design with carbon nanostructured materials, and tunable electrocatalytic studies, are discussed. A key focus is the synthesis of small CZTS nanoparticles with tunable reactivity, emphasizing the sonochemical method's role in their formation. Despite CZTS's affordability, it often exhibits poor hydrogen evolution reaction (HER). Carbon materials are highlighted for their ability to enhance electrocatalytic activity due to their unique properties. The review also discusses the amine functionalization of graphene oxide/CZTS composites, which enhances overall water splitting. Doping with non-noble metals is presented as an effective strategy to improve catalytic activity. Additionally, the synthesis of heterostructures consisting of CZTS nanoparticles attached to MoS2-reduced graphene oxide(rGO) hybrids is explored, showing enhanced HER activity compared to pure CZTS and MoS2. The growing demand for energy and the need for efficient renewable energy sources, particularly H2 generation, are driving research in this field. The review aims to demonstrate the potential of CZTS-based electrocatalysts for high-performance and cost-effective H2 generation with low environmental impact. Methods for fabricating CZTS are discussed, with a focus on simplicity and efficiency. Future developments in CZTS-based electrocatalysts include enhancing activity and stability, improving charge transfer mechanisms, ensuring cost-effectiveness and scalability, increasing durability, integrating with renewable energy sources, and gaining deeper insight into reaction processes. Overall, CZTS-based electrocatalysts show great promise for sustainable H2 generation, with ongoing research focused on improving performance and advancing their practical applications.